النظام أحكام الشريعة الإسلامية في إندونسيا - Evi Alfiatur Rohmah; Mohammad Nu’man (Sekolah Tinggi Ilmu Tarbiyah Al-Hilal Sigli Aceh- Indonesia, 2023)
The dominant characteristics of Indonesian Islamic law are characterized by Arab personality (Arabic orientation) and are more attached to the tradition of the Shafi'i school of thought. Reforming a comprehensive and integrated national legal system by recognizing and respecting religious law and customary law and renewing discriminatory colonial and national heritage legislation, including unfair rights fulfillment and their incompatibility with demands for reform through legislation. Islamic law can be made the main source in the formation of national law in Indonesia. The application of formally juridical Islamic law has actually taken place in Indonesia, however, the applicable Islamic law is still partial, namely Islamic civil law